Gap Analysis in Adoption of Recommended Package of Practices of Paddy Cultivation under Temperate Climatic Conditions of Kashmir (Indian Journal of Extension Education, 2018)
A survey was conducted in Zaingeer Block of Baramulla District of Jammu and Kashmir state with the view to explore the extent of adoption of recommended package of practices for cultivation of paddy and the constraints faced by the farmers. A sample of 60 respondents was selected using random sampling technique. A good number of the farmer followed the recommendations of the scientists either partially or fully in paddy crop. 63.30 percent of farmers used high yielding varieties, 66.7 per cent farmers did not follow proper sowing time. Fifty percent of the farmers had adopted partial spacing, 43.3 per cent of farmers apply basal dose of nitrogen and 40 per cent apply top dressing as per the recommendations. But majority 53.3 per cent and 63.3 per cent of the farmers did not follow the recommendation in the application of DAP and MoP respectively. The major constraints faced by the farmers in adoption of recommended package of practice were lack of skill in seed treatment (90%), lack of technical advice for seed storage (88.33%), irregular visits of Agricultural Officers (86.66%), low rate of Paddy in local market (83.33%), inadequate and untimely disbursement of loans (81.67%), high seed rate (71.67%) and high cost of fertilizers (68.33%) are important factors mainly responsible of low yield of rice.